Isolation and characterization of new phenolic siderophores with antimicrobial properties from Pseudomonas sp. UIAU-6B - Oluwabusola, Emmanuel Tope; Adebisi, Olusoji O.; Reyes, Fernando; Acquah, Kojo S.; De La Cruz, Mercedes; Mweetwa, Larry L.; Rajakulendran, Joy E.; Warner, Digby F.; Hai, Deng; Ebel, Rainer; Jaspars, Marcel (Beilstein Journal of Organic Chemistry, 2021)
Five new phenolic siderophores 1–5 were isolated from the organic extract of a culture broth in a modified SGG medium of Pseudomonas sp. UIAU-6B, obtained from sediments collected from the Oyun river in North Central Nigeria. The structure of the new compounds, pseudomonin A–C (1–3) and pseudomobactin A and B (4 and 5) isolated alongside two known compounds, pseudomonine (6) and salicylic acid (7), were elucidated based on high-resolution mass spectrometry, 1D and 2D NMR analyses. The absolute configuration of the threonine residue in compounds 1–5 was determined by Marfey analysis. The antimicrobial evaluation of compound 4 exhibited the most potent activity against vancomycin-sensitive Enterococcus faecium VS144754, followed by 3 and 5, with MIC values ranging from 8 to 32 µg/mL. Compounds 2 and 3 exhibited moderate activity against Mycobacterium tuberculosis H37Rv, with MIC values of 7.8 and 15.6 µg/mL, respectively. Plausible biosynthetic hypotheses toward the new compounds 1–5 were proposed.
Keywords: Mycobacterium tuberculosis; Phenolic siderophores; pseudomonine; Pseudomonas sp.; vancomycin-sensitive Enterococcus faecium